Fault Detection in Sugarcane Crop Lines Using Hough Transform - Carneiro, Alexsandro M.; Higa, Gabriel T. H.; Rodrigues, Alexandre G. de O.; M. Junior, José; Pistori, Hemerson (Anais do Workshop de Visão Computacional (WVC); 2023: Anais do XVIII Workshop de Visão Computacional, 2023)
In this work, we present an algorithm for detecting faults in sugarcane planting rows using the Hough transform, supported by image pre-processing techniques, such as binarization, morphological operators, filters, and skeletonization. Seven preprocessing calibration parameters are investigated. For the calibration and testing of the proposed method, a set of images with 589 samples, captured by UAV in an area located in Nova Andradina, MS, is presented.